The Influence of Word of Mouth on Purchasing Decisions for Wardah Cosmetic Products with Communication Media as a Mediating Variable - Eko Santoso; Desi Rahmawati (Citakonsultindo, 2024)
This research aims to describe the influence of word of mouth on purchasing decisions for Wardah Cosmetic products with communication media as a mediating variable. The research method used in this research is a quantitative approach. Data processing in this research uses smartPLS SEM (Partial et al. - Structural Equation Modeling) software. PLS can explain the relationship between variables and the ability to conduct analyses in one test. To test the hypothesis using statistical values, for alpha 5%, the t-statistic value used is 1.96. Research results. The results of testing the first hypothesis were accepted that Media Communication (Z) affected buying decisions (Y). The results of testing the second hypothesis were accepted that Word of Mouth (X) had an effect on buying decisions (Y). The results of testing the third hypothesis are accepted that Word of Mouth (X) influences Media Communication (Z). The results of testing the fourth hypothesis were accepted. Word of Mouth (X) had a significant effect on buying decisions (Y) via Media Communication (Z).